Anxiety disorders - Kase, Larina (John Wiley & Sons, 2007)
Like all the books in the Wiley Concise Guides to Mental Health Series, Anxiety Disorders features a compact, easy-to-use format that includes: Vignettes and case illustrations; A practical approach that emphasizes real-life treatment over theory; Resources for specific readers such as clinicians, students, and patients